Adoptive transfusion of tolerance dendritic cells prolongs the survival of skin allografts in mice: a systematic review. Issue 2 (28th May 2013) - Zhou, Yanni; Shan, Juan; Li, Youping; Guo, Yingjia; Sun, Guixiang; Yang, Tong; Xia, Mengjuan; Feng, Li
Abstract Objective We aim to systematically review adoptive transfusion of tolerogenic dendritic cells (Tol‐DCs) induced by different ways to affect skin allograft survival in mice. Methods We searched PubMed and EMbase for relevant studies and evaluated the quality of included ones. Taking skin allograft survival time as endpoint outcome, we displayed outcomes of each group using one forest map and dissected possible mechanisms underlying survival prolongation. Results We included 21 studies, which reported four methods of inducing Tol‐DCs with different extents of average allograft survival prolongation: skin allograft survival time was prolonged (the drug intervention group, 63.08 ± 42.92 days, 4.6 folds to control; the cytokine induction group: 26.17 ± 16.20 days, 1.8 folds; the gene modification group: 14.65 ± 17.89 days, 1.5 folds; other derivation group 9.63 ± 24.38 days, 0.5 fold). Possible mechanisms underlying survival prolongation included induction of donor‐specific T cell hyporesponsiveness, reduction of cytotoxicity against allografts, Th0 skewing to Th2, and generation or expansion of Treg. Infusion of Tol‐DCs in combination with immunosuppressive agents or costimulatory blockade contributed to longer prolongation. Compared to MiHA mismatch, MHCI/II mismatch was a much more important factor to cause skin allograft rejection. Conclusion For MHC or MiHA mismatched, allogeneic skin transplants inbred recipients, adoptive transfusion of Tol‐DCs induced by 4 methods prolong skin allograft survival to different extents. Drug intervened Tol‐DCs works best. Immunosuppressive agents and/or co‐stimulatory blockade contribute to better outcomes. Yet more rigorous studies with larger sample size are needed and more attention to mechanisms should be paid.